2011
DOI: 10.1177/0956797611401752
|View full text |Cite
|
Sign up to set email alerts
|

Low- and High-Testosterone Individuals Exhibit Decreased Aversion to Economic Risk

Abstract: Testosterone is positively associated with risk-taking behavior in social domains (e.g., crime, physical aggression). However, the scant research linking testosterone to economic risk preferences presents inconsistent findings. We examined the relationship between endogenous testosterone and individuals’ economic preferences (i.e., risk preference, ambiguity preference, and loss aversion) in a large sample (N = 298) of men and women. We found that endogenous testosterone levels have a significant U-shaped asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
66
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(75 citation statements)
references
References 31 publications
6
66
1
2
Order By: Relevance
“…As with dominance and aggression, however, the evidence relating T to risk-taking and competition is far from conclusive. For instance, Apicella et al (2008) find a positive correlation between T and risk-taking in men, but Sapienza et al (2009) find that such correlation is only present in women, and Stanton et al (2011) observe a U-shaped relationship whereby both low and high T individuals exhibit greater risk taking. Similarly, whereas Mehta and Josephs (2006) and Carré and McCormick (2008) found that endogenously elevated T in men correlated with increased competitiveness, Apicella et al (2011) found no correlation between competitiveness and men's basal T and Mehta and Josephs (2010) found this correlation only to be present in men with low cortisol.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…As with dominance and aggression, however, the evidence relating T to risk-taking and competition is far from conclusive. For instance, Apicella et al (2008) find a positive correlation between T and risk-taking in men, but Sapienza et al (2009) find that such correlation is only present in women, and Stanton et al (2011) observe a U-shaped relationship whereby both low and high T individuals exhibit greater risk taking. Similarly, whereas Mehta and Josephs (2006) and Carré and McCormick (2008) found that endogenously elevated T in men correlated with increased competitiveness, Apicella et al (2011) found no correlation between competitiveness and men's basal T and Mehta and Josephs (2010) found this correlation only to be present in men with low cortisol.…”
Section: Introductionmentioning
confidence: 97%
“…For instance, it has been suggested that T might be an important biological determinant of gender differences in negotiation, competition and risk-taking (Croson and Gneezy, 2009;Marianne, 2011). Indeed, T has been shown to be significantly correlated with financial risk-taking (Apicella et al, 2008(Apicella et al, , 2014(Apicella et al, , 2015Sapienza et al, 2009;Stanton et al, 2011), willingness to compete (Mehta and Josephs, 2006;Carré and McCormick, 2008) and with the likelihood of pursuing a career in finance (Sapienza et al, 2009), whereas lower second-to-fourth digit ratios (2D4D) -a postulated indicator of high prenatal androgens (Manning et al, 1998) -has been found to predict long-term profits in professional traders (Coates et al, 2009). As with dominance and aggression, however, the evidence relating T to risk-taking and competition is far from conclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Neither Eisenegger et al (2010) nor Zethraeus et al (2009) find a significant effect of exogenously received testosterone on ultimatum game responder behavior, but Eisenegger et al (2010) find that women who exogenously received testosterone made fairer offers in the ultimatum game. Further, while Apicella et al (2008) find that testosterone correlates positively with risk taking in men, Sapienza et al (2009) only find some evidence of this among women and not men, and Stanton et al (2011) find a nonlinear relation in a mixed-sex sample. However, Zethraeus et al (2009) find no effect on risk taking in a sample of postmenopausal women who received an exogenously administered dose of testosterone.…”
mentioning
confidence: 98%
“…Recall that based on findings by Stanton et al (2011b) we hypothesized that essentially the number of choices of lottery A should be "concave" in salivary testosterone. When we include as an additional the square of the testosterone measure in specifications analogous to G3F and L3F, both the coefficient for the testosterone measure and the coefficient for the squared testosterone measure are insignificant.…”
Section: Observation 4 (Males)mentioning
confidence: 99%